Silk-based biomaterials functionalized with fibronectin type II promotes cell adhesion - Pereira, A. M. (2017)
The objective of this work was to exploit the fibronectin type II (FNII) module from human matrix metalloproteinase-2 as a functional domain for the development of silk-based biopolymer blends that display enhanced cell adhesion properties. The DNA sequence of spider dragline silk protein (6mer) was genetically fused with the FNII coding sequence and expressed in Escherichia coli. The chimeric protein 6mer + FNII was purified by non-chromatographic methods. Films prepared from 6mer + FNII by solvent casting promoted only limited cell adhesion of human skin fibroblasts. However, the performance of the material in terms of cell adhesion was significantly improved when 6mer + FNII was combined with a silk-elastin-like protein in a concentration-dependent behavior. With this work we describe a novel class of biopolymer that promote cell adhesion and potentially useful as biomaterials for tissue engineering and regenerative medicine. Statement of Significance This work reports the development of biocompatible silk-based composites with enhanced cell adhesion properties suitable for biomedical applications in regenerative medicine. The biocomposites were produced by combining a genetically engineered silk-elastin-like protein with a genetically engineered spider-silk-based polypeptide carrying the three domains of the fibronectin type II module from human metalloproteinase-2. These composites were processed into free-standing films by solvent casting and characterized for their biological behavior. To our knowledge this is the first report of the exploitation of all three FNII domains as a functional domain for the development of bioinspired materials with improved biological performance. The present study highlights the potential of using genetically engineered protein-based composites as a platform for the development of new bioinspired biomaterials.